The Etiology, Classification, and Management of Shock: A Review - Tita Agrippina Indira Hapsari; Deasy Fetarayani; Fatrian Dwicahya; Naufalluthfi Widodo (Current Internal Medicine Research and Practice Surabaya Journal, 2026)
Abstract Shock is a critical condition characterized by circulatory failure that results in inadequate oxygen delivery and may lead to organ dysfunction, and it is classified into four main types—hypovolemic, cardiogenic, distributive, and obstructive shock—each with distinct pathophysiological mechanisms. This review aims to provide a comprehensive overview of the etiology, classification, and management of the various types of shock, with an emphasis on the importance of early recognition and timely intervention to prevent irreversible organ damage and mortality. The results highlight the crucial role of early diagnosis through thorough history-taking, physical examination, and targeted investigations, as well as advances in fluid management, pharmacological therapies, and bedside assessment tools that have improved the ability to stabilize patients promptly and effectively, although challenges remain in optimizing individualized treatment protocols. Furthermore, a multidisciplinary approach combined with adherence to established guidelines is essential to enhance patient outcomes and reduce mortality. In conclusion, prompt identification and intervention are fundamental to effective shock management, and continued advancements in treatment strategies along with ongoing research into personalized care are vital for improving outcomes in patients with shock.